Efficacy and Safety of a Weight-based Dosing Regimen of Valganciclovir for Cytomegalovirus Prophylaxis in Pediatric Solid-organ Transplant Recipients. Issue 8 (August 2019) - Pappo, Adi; Peled, Orit; Berkovitch, Matitiahu; Bilavsky, Efraim; Rom, Eran; Amir, Jacob; Krause, Irit; Yarden-Bilavsky, Havatzelet; Scheuerman, Oded; Ashkenazi-Hoffnung, Liat
Abstract : Background: Valganciclovir has been widely used for cytomegalovirus (CMV) prophylaxis in solid-organ transplant recipients. However, the optimal dosing protocol and target exposure in children are still unclear. Specific data as to the efficacy and safety of low-dose/low-exposure regimens are lacking and urgently needed. Methods: During 2010 to 2015, the clinical efficacy and safety of a weight-based regimen of valganciclovir of 17 mg/kg/day, with a stratified dose reduction for impaired creatinine clearance, given as a CMV prophylaxis for 3 to 6 months, was retrospectively evaluated among pediatric kidney and liver transplant recipients, 12 months posttransplantation. Incidence of CMV infection was assessed by periodic measurements of viral load; adverse events were evaluated. Results: Eighty-three children who had undergone 86 transplantations and were treated with 17 mg/kg of valganciclovir were included. Median age was 9.77 years (range, 0.6 to 18.9). Twelve (14%) developed CMV infection: 1 during prophylaxis and 11 during follow-up. These events comprised 6 cases of asymptomatic viremia and 6 cases of a clinically significant disease without occurrences of tissue-invasive disease. Treatment-related adverse effects occurred in 7 patients (8%), mostly hematological, resulting in premature drug cessation. Conclusions: Our results support the use of 17 mg/kg of valganciclovir for CMV prophylaxis in liver and kidney transplanted children as it showed satisfactory long-term efficacy and a good safety profile.